Deciphering the intricate mechanisms behind the selective oxidation of methane to C1 and C2 oxygenates over FeAu/γ-Al2O3 catalysts - Prabu, Marimuthu; Manikandan, Marimuthu; Rengam, B. Sathya Sai; Ramakrishnan, Archana; Raja, Abhishekram; Urkude, Rajashri R.; Ghosh, Biplab; Varghese, Jithin John; Raja, Thirumalaiswamy (Chemical Engineering Journal, 2025)
In this work, we demonstrate an eco-benign synthesis protocol for preparing gold nanoparticles and the role of the strong interaction between gold nanoparticles and iron oxide in FeAu/gamma-Al2O3 catalysts that render it an anionic (Au delta-) character while tailoring them in a smaller size. The multifunctional FeAu/gamma-Al2O3 catalyst selectively produces ethanol (95 % selectivity, similar to 240 mu mol(-1) cat) at a mild temperature of 75 degrees C without the addition of co-reactants during liquid phase methane oxidation with molecular oxygen. Conversely, Au/gamma-Al2O3 and Fe/gamma-Al2O3 catalysts exhibited high selectivity for CH3OH and HCHO. A high dispersion accompanied by strong electronic interaction between the Au delta–FeOx, as corroborated by diverse techniques, enables methane activation across the interface and coupling on the gold nanoparticles, which are responsible for the markedly improved formation of ethanol. Furthermore, in situ DRIFTS studies and DFT investigations point to a reaction mechanism of coupling of CH2OH and CH3 intermediates as the most likely route for ethanol formation.
Keywords: Anionic gold catalysts; Au-FeOx synergism; C-H bond activation; Ethanol; Methane oxidation; Methanol